2004
DOI: 10.2486/indhealth.42.424
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Occupational Injuries in the Construction Sector in Kocaeli, Turkey, 1990-2001

Abstract: In Turkey, the construction sector is responsible for the largest number of work-related fatalities among all industries. This study's objective is to determine the characteristics of the fatalities in the construction sector in Kocaeli Province. The study was carried out retrospectively by investigating the records of occupational deaths between 1990 and 2001 in the Kocaeli District of Turkey. Fatal occupational injuries in the construction sector were investigated in detail by evaluating the records. The ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 19 publications
6
42
0
Order By: Relevance
“…However, in the construction sector, a worker can be employed even before "the paperwork" has been completed. Employers misuse this legal gap, and initiate legal insurance procedure on the day the accident occurs 2) . If this is the case, then it may be suggested that since there are thousands of workers in the construction sector, working without insurance and as they are not recorded officially, not only for motor vehicle or equipment accidents but also for all types of construction accidents, statistics cannot be accurate.…”
Section: Researchers Should Be Aware Of the Lack Of Data When Dealingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the construction sector, a worker can be employed even before "the paperwork" has been completed. Employers misuse this legal gap, and initiate legal insurance procedure on the day the accident occurs 2) . If this is the case, then it may be suggested that since there are thousands of workers in the construction sector, working without insurance and as they are not recorded officially, not only for motor vehicle or equipment accidents but also for all types of construction accidents, statistics cannot be accurate.…”
Section: Researchers Should Be Aware Of the Lack Of Data When Dealingmentioning
confidence: 99%
“…Approximately 72,000 occupational accidents occur each year, and approximately 1,000 of these cases end with deaths. In addition to this, about 90% of occupational accidents result in temporary disability, whilst 2.5-3.5% results in permanent disability 2) . In Table 1, it can be seen that between years 1992 and 2002, the average incidence rate of fatal injuries is 56.4 per 100,000 workers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was consisting with results of previous research which were conducted in several fields. For example, colak, Bahrampoor and vatani-shoja et al had reported that fractures were more than 70% percent of accidents consequences in their studies (11,13,14). Highest frequencies of causes of accidents were carelessness with the frequency of 280 cases 80.69%) and deficiency or lack of suitable fence, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Colak et al [14] evaluated the characteristics of occupational injuries for construction employees in the Kocaeli Province (Turkey), suggesting that small companies should be checked more systematically and should be encouraged to properly train their workers with regard to safety. Cheng et al [15] focused on analyzing the accident patterns of small construction enterprises in Taiwan and discovered that most of the accidents in small construction companies occurred in non-governmental projects with contract prices below 5 million NTD (New Taiwan Dollars).…”
Section: Introductionmentioning
confidence: 99%